Is it worth it? - a phenomenological analysis of the willingness to take interpersonal risk - Novak, A. Boyd, author; Chermack, Thomas, advisor; Lynham, Susan A., committee member; Maynard, Travis, committee member; Thomas, Cliff, committee member (Colorado State University. Libraries, 2025)
Developing and implementing new technologies are essential parts of our economic system. Organizations aim to improve career information technology (IT) project success and reduce costs. Late-stage career professionals are valuable assets for organizations to leverage in delivering these projects and capabilities to consumers. Yet, how do organizations get the most from these employees? This study explored the lived experiences of late-stage career (IT) professionals as they navigated interpersonal risk in group settings. Grounded in psychological safety, psychological availability, and resources, the research employed Interpretative Phenomenological Analysis (IPA) to provide deeper insights into these experiences than prior quantitative studies. Data were collected through semi-structured interviews with ten participants. The experiences were analyzed to identify Personal Experiential Themes (PETs), consolidated into seven Group Experiential Themes (GETs): identity, reflections, norms, dilemma, control, boundaries, and resources. The findings indicate that participants approached risky situations with a strong sense of self-identity, shaped by their past experiences and the influence of established norms. When faced with dilemmas, participants aimed for control through organized processes but often encountered difficulties concerning personal boundaries, necessitating careful resource management and decisions about risk engagement. Additionally, the study highlighted two critical resources, reputation and net wealth, which impacted participants' willingness to engage in risky situations. Reputation emerged as a vital social asset related to career longevity, while net wealth indicated future economic security and life expectations. The findings introduce a resource framework to identify the most operative resources for the individuals involved in the study, which may aid future research and HRD practitioners in better understanding and prioritizing interventions and their development. This research enhances our understanding of how people navigate interpersonal risks, offering insights that can improve employee and leadership development programs, organizational structures, and workplace culture. It provides practical recommendations to create environments that support psychological safety and ensure resource availability, boosting performance, retention, and organizational success. The study concludes with recommendations for future research and reflections on the research journey.
Keywords: psychological availability; resources; psychological safety; interpretative phenomenological analysis